The Influence of Compensation on Employee Performance at PT. Mitra Ekasari Jaya Putri Sumedang - Dewi Anggini, Megah; Amanda, Helles; Apriani, Via (Jurnal Ekuisci, 2024)
Abstract. This research was conducted at PT. Mitra Ekasari Jaya Putri Sumedang to evaluateemployee performance which was thought to be influenced by compensation. The purpose of thisresearch is to understand compensation conditions, employee performance, and the influence ofcompensation on employee performance in the company. The method applied was a survey withquantitative analysis using a Likert scale and involving 35 respondents as a sample. The results ofthe analysis using SPSS 26 show a coefficient of determination (R-squared) of 0.435, which meansthat compensation influences employee performance by 43.5%, while 56.5% is influenced by otherfactors not studied. Simple linear regression analysis produces a model: employee performance =34,096 + compensation 0.477. The t test shows the calculated t value of 5.038, which is greater thanthe t table of 2.030, with a significance value (Sig) of 0.000 which is smaller than 0.05. Apart fromthat, the correlation coefficient shows a calculated r value of 0.659, exceeding the table r value of 0.334,with a significance (2-tailed) of 0.000 which is also smaller than 0.050. Based on these results, it can beconcluded that compensation has a positive influence on employee performance at PT Mitra Ekasari Jaya PutriSumedang